Peran Pendampingan Keluarga Dalam Senam Diabetes Pada Penderita Diabetes Di Puskesmas Sekargadung - Aristawati, Evy; Puspitasari, R.A. Helda (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2020)
Diabetes Mellitus is often referred to as the great imitator, because it can affect all organs of the body and cause various complaints. Diabetes Mellitus can arise slowly so patients are not aware of changes such as drinking more frequent miktion. The aim of the study is to describe the role of family in the implementation of diabetes gymnastics in patients with Diabetes Mellitus (DM) type 2 at Gayungan Health Center Village Dukuh Denied Surabaya.This research design using descriptive research. The population is all families who have family members with cases of diabetes mellitus with a large sample of 4O people. Sampling using technique Total sampling The variables studied is the role of kleuarga in the implementation of diabetes gymnastics. Data collection was done by distributing questionnaires.The results showed that from 40 respondents in Gayungan Public Health Center, Dukuh Menanggal Surabaya, almost half of them play a good role in the implementation of diabetes gymnastics in diabetic patients as much as 40% (16 people).Health workers should improve health services by providing counseling - extension on diabetics millitus and their families.Keywords: Role Family, Diabetes Mellitus, Gymnastics